In- vitro antibacterial activity and phytochemical screening of bioactive compounds from pomegranate (Punica granatum L.) crude peel extracts - Khaleel, Ayad Ismael (2016)
Plant pathogenic bacteria are recognized to be harmful microbes able to decrease the quantity and quality of crop production in agriculture. Punica granatum L. peel was screened for its potential use as a biological control agent for plant pathogenic bacteria. P. granatum peel was successfully extracted using n-hexane, methanol and ethyl acetate. The highest percentage of crude extracts was obtained from ethyl acetate 1.37% followed by methanol crude extracts 1.17% and n-Hexane 0.89%. The highest yield obtained by ethyl acetate showed that ethyl acetate extracted more compounds that are readily soluble to methanol and n-hexane. For in-vitro antibacterial activity, three different species of plant pathogenic bacteria were used namely Erwinia carotovorum subsp. carotovorum, Ralstonia solanacearum, and Xanthomonas gardneri. For all crude extracts, four different concentrations of 25, 50, 100 and 200 mg/mL were used in cup-plate agar diffusion method. Streptomycin sulfate at concentration 30 μg/mL was used as positive control while each respective solvent used for peel extraction was used as a negative control. The results obtained from in vitro studies showed only ethyl acetate extract possessed antibacterial activity tested on the plant pathogenic bacteria. Methanol and n-hexane did not show any antibacterial activity against plant pathogenic bacteria selected where no inhibition zones were recorded. R. solanacearum recorded the highest diameter of inhibition zone for all ranges of concentrations introduced followed by P. carotovorum subsp. carotovorum and X. gardneri. For the minimum inhbitory concentration (MIC) and minimum bactericidal concentration (MBC), only the ethyl acetate extract was subjected to the assay as only ethyl acetate extract exhibited antibacterial activity. The minimum concentration of ethyl acetate extract that was able to inhibit plant pathogenic bacteria was recorded at a concentration of 3.12 mg/mL, which inhibited R. solancearum and P. carotovorum subsp. carotovorum, followed by X. gardneri at concentration of 6.25 mg/mL. For the minimum bactericidal concentration (MBC), the results showed that at the concentration of 12.5 mg/mL, the extract was still capable of killing the pathogenic bacteria, R. solanacearum, and P. caratovora sub.sp. caratovora while for the bacteria X. gardneri, the concentration that was able to kill the bacteria was 25 mg/mL. The qualitative estimation of phytochemical constituents within P. granatum ethyl acetate peel extracts revealed the presence of tannins, flavonoids, phenols alkaloid, Saponins, and terpenoids. The thin layer chromatography (TLC) profiling of ethyl acetate extract using hexane, ethyl acetate, and chloroform with ratio 5:3:2 (v/v) gave eleven maximum colorful bands when visualized under short UV wavelength (254nm), six bands under long UV wavelength (365nm) and eight bands in daylight (normal light) with different retention factors, and Rf values that provined the presence of various secondary metabolites within ethyl acetate extract. The antibacterial activity of ethyl acetate peel extract was also screened through direct bioautography technique in order to detect the location of the progressive band on chromatograms developed in the same substance for TLC profiling. The recorded active Rf values that inhibited all selected plant pathogenic bacteria at the same Rf values location were 0.45, 0.83 and 0.92. The GC-MS spectrum range affirmed the vicinity of 292 different components with diverse retention times and chemical structure eleven elements in the high peak chosen were (DMSO; n-Hexadecanoic acid; 9,12-Octadecadienoic acid (Z,Z); cis-Vaccenic acid; Octadecanoic acid; Pentanoic acid; cis-9-Hexadecenoic acid; Tetradecanoic acid; 2-Heptenoic acid; Octanal diethyl acetal; Glycerin). The results obtained from this study suggest that P. granatum L ethyl acetate peel extracts have the potential to be industrialized as a novel bactericide.